ANALISA SISTEM PENDUKUNG KEPUTUSAN MENGGUNAKAN METODE TOPSIS UNTUK SISTEM PENERIMAAN PEGAWAI PADA SMA AL WASHLIYAH TANJUNG MORAWA - Sriani Sriani; Raissa Amanda Putri (Universitas Islam Negeri Sumatera Utara, 2018)
Decision support system is a system that is able to solve problems efesian, effectively, which aims to help make decisions by choosing a variety of alternative decisions. With the software implemented hiring decision support system by using TOPSIS method to facilitate decision-making in SMA Al Washliyah Tanjung Morawa. The program used role in this system is Microsoft Visual Studio 2008 by using a MySQL database as the tools used for the testing process. The results of this program show that the progress of science and technology, each job can be more efficiently and effectively. The program is expected to provide a solution or settlement of the existing problems, thus adding to the treasury of the new science. Keywords:Decision support system, TOPSIS